Tuberculous cervical lymphadenitis (scrofula): USG, doppler and elastographic evaluation: report of two cases - Phatak, Suresh V.; Gupta, Nipun; Phatak, Pallavi (International Journal of Research in Medical Sciences, 2017)
Lymphadenitis is the most generic form of extra pulmonary manifestation of tuberculosis. It is both diagnostic and therapeutic challenge because it mimics various other pathologic processes and yields inconsistent physical laboratory findings. Diagnosis is quite difficult often requiring biopsy. It is also important to differentiate tuberculous from non-tuberculous mycobacterial cervical lymphadenitis as their treatment protocols are different. We are presenting a case report of two patients who presented with neck swelling. Elastography is a recent advance in the field of sonography helping in identifying nature of pathology. Sonography, doppler and elastographic findings are discussed.